THE RELEVANCE OF ODD-EVEN VERSES IN THE QUR’AN WITH MATHEMATICS EDUCATION - Surur, Agus Miftakus; Pujilestari, Sri (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2021)
Education is an effort to improve knowledge, one of which is by conducting studies on the Qur'an and Mathematics. This research examines the verses of the Qur'an containing odd-even concepts and their relevance to mathematics. By using the library research method, the verse selection step is taken from observations of the translated Qur'an. The mathematical concepts found are materials related to odd-even concepts, such as KPK (Least Common Multiple) and FPB (Greatest Common Factor), Venn diagrams, and Phi in ṭawwāf. As the result, the number of verses and the number of surahs show odd-even numbers. If the numbers are added up to 38, these will be equal to the number of letters in the syahādah sentence.